Comparative analysis of process-induced strain glass states in austenitic and martensitic NiTi shape memory alloy plates - John, Neha S.; Ashmore, Bailey; Wall, Michael T.; Wheeler, Robert W.; Young, Marcus L.; Giri, Anit K. (Frontiers in Metals and Alloys, 2023)
Strain glass alloys (SGAs) are metallic alloys with glassy martensitic nano-domains within a crystalline material, which occur from processing-or compositionally-induced strain. SGAs originate from shape memory alloys (SMAs) and exhibit similar shape memory properties and high actuation densities. The transition from SMA to SGA is relatively unexplored, and although there are similarities with amorphous SMAs and cold-worked SMAs, SGAs should be distinguished as a separate grouping. The transition occurs by interrupting the long-range martensitic order, which in turn disrupts the martensitic transformation, resulting in short-range martensitic order. A glassy martensitic phase is produced, which exhibits enhanced structural and load bearing abilities, functional stresses, and recoverability.In this study, the transformation from SMA to SGA is explored in two common commercially available SMAs, Ni49.5Ti50.5 and Ni50.8Ti49.2 (at. %), to compare martensitic versus austenitic SGAs, respectively. SMA plates were cold worked in 5% increments until a strain glass transition occurred. Characterization of the samples at various stages of cold work were examined via differential scanning calorimetry (DSC), Vickers hardness, transmission electron microscopy (TEM), and synchrotron radiation x-ray diffraction (SR-XRD). Some of the prominent characteristics such as enthalpy peaks, twin size reduction, and crystallographic structure between the two plates were examined and compared to improve the understanding of the SMA to SGA transition.